Expanding the genetic spectrum of mitochondrial diseases in Tunisia: novel variants revealed by whole-exome sequencing - Gouiza, Ismail; Hechmi, Meriem; Zioudi, Abir; Dallali, Hamza; Kheriji, Nadia; Charif, Majida; Le Mao, Morgane; Galai, Said; Kraoua, Lilia; Ben Youssef-Turki, Ilhem; Kraoua, Ichraf; Lenaers, Guy; et al. (Frontiers in Genetics, 2024)
Introduction: Inherited mitochondrial diseases are the most common group of metabolic disorders caused by a defect in the oxidative phosphorylation. They are characterized by a wide clinical and This is a provisional file, not the final typeset article genetic spectrum and can manifest at any age. In this study, we established novel phenotype-genotype correlations between the clinical and molecular features of a cohort of Tunisian patients with mitochondrial diseases. Materials and Methods: Whole Exome Sequencing was performed on five Tunisian patients with suspected mitochondrial diseases. Then, a combination of filtering and bioinformatics prediction tools were utilized to assess the pathogenicity of genetic variations. Sanger sequencing was subsequently performed to confirm the presence of potential deleterious variants in the patients and verify their segregation within families. Structural modeling was conducted to study the effect of novel variants on protein structure. Results: we identified two novel homozygous variants in NDUFAF5 (c.827G>C; p.Arg276Pro) and FASTKD2 (c.496_497del; p.Leu166GlufsTer2) associated with a severe clinical form of Leigh and Leigh-like syndromes, respectively. Our results further disclosed two variants unreported in North Africa, in GFM2 (c.569G>A; p.Arg190Gln) and FOXRED1 (c.1261G>A; p.Val421Met) genes and we described the first case of Fumaric aciduria in a Tunisian patient harboring the c.1358T>C; p.Leu453Pro FH variant. Conclusion: Our study expands the mutational and phenotypic spectrum of mitochondrial diseases in Tunisia and highlights the importance of Next Generation Sequencing next generation sequencing (NGS) to decipher the pathomolecular mechanisms responsible for these disorders in an admixed population.